Increased pentane and carbon disulfide in the breath of patients with schizophrenia. - Michael Phillips; M Sabas; Joel Greenberg (1993)
To determine the concentrations of pentane (a marker of lipid peroxidation) and other volatile organic compounds in the breath of patients with schizophrenia.Volatile organic compounds were assayed by gas chromatography/mass spectroscopy (GC/MS) in 88 subjects--25 with acute schizophrenic psychosis, 26 with psychiatric disorders other than schizophrenia, and 37 normal volunteers.The mean alveolar gradients of pentane and carbon disulfide (CS2) were significantly higher in the patients with schizophrenia than in the control groups.Schizophrenia may be accompanied by accelerated lipid peroxidation in cell membranes, as well as increased manufacture of CS2, a known neurotoxin.